mTOR expression and activity patterns in gastroenteropancreatic neuroendocrine tumours - Kasajima, Atsuko; Pavel, Marianne; Darb-Esfahani, Silvia; Noske, Aurelia; Stenzinger, Albrecht; Sasano, Hironobu; Dietel, Manfred; Denkert, Carsten; Röcken, Christoph; Wiedenmann, Bertram; Weichert, Wilko (Endocrine related cancer, 2011)
Clinical trials indicate efficacy of drugs inhibiting the mammalian target of rapamycin (mTOR) in the treatment of gastroenteropancreatic neuroendocrine tumours (GEP-NET); however, information on detailed expression and activity patterns of mTOR in these tumours is sparse. We investigated the expression of mTOR and expression as well as phosphorylation of its downstream targets 4EBP1, S6K and eIF4E in a cohort of 99 human GEP-NET by immunohistochemistry. We correlated our findings with clinicopathological variables and patient prognosis. We found that 61, 93, 80, 69, 57 and 79% of GEP-NET were positive for mTOR, 4EBP1, cytoplasmic phospho-4EBP1 (p-4EBP1), nuclear p-4EBP1, phospho-S6K (p-S6K) and phospho-eIF4E (p-eIF4E) respectively. mTOR expression and activity were higher in foregut than in midgut tumours. In foregut tumours, expression of mTOR was higher when distant metastases were present (P=0.035). Strong mTOR activity was associated with higher proliferative capacity. In patients with stage IV midgut tumours, strong p-S6K expression was associated with poor disease-specific survival (P=0.048). In conclusion, mTOR shows considerable variations in expression and activity patterns in GEP-NET in dependence of tumour location and metastatic status. We hypothesise that these differences in mTOR expression and activity might possibly influence response to mTOR inhibitors.